(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the pre-training and post-training training of wrestlers, training in technical and tactical techniques during training, and the development of the sport of wrestling. The main part of the textbook deals with the types, types of wrestling: judo, sambo, Greco-Roman, freestyle and Uzbek national wrestling, their origin, history, rules, methods and techniques. The participants were also analyzed for theoretical, technical, physical, strategic and tactical training, as well as arbitration tasks and integrated training, which provided insights into the methods of training wrestlers of all weight classes.